Fabrication, Characterization and low-velocity impact testing of hybrid sandwich composites with polyurethane/layered silicate foam cores - Njuguna, James A. K.; Michalowski, Slawomir; Pielichowski, Krzysztof; Kayvantash, Kambiz; Walton, A. C. (John Wiley & Sons, Ltd, 2011)
A series of nanophased hybrid sandwich composites based on polyurethane/montmorillonite (PU/MMT) has been fabricated and characterised. Polyaddition reaction of the polyol premix with 4,4'-diphenylmethane diisocyanate was applied to obtain nanophased polyurethane foams which were then used for fabrication of sandwich panels. It has been found that the incorporation of MMT resulted in higher number of PU cells with smaller dimensions and higher anisotropy index (cross-sections RI and RII). The obtained materials exhibited improved parameters in terms of thermal insulation properties. The results also show that nanophased sandwich structures are capable of upholding withstanding higher peak loads than those made of neat polyurethane foam cores when subject to low-velocity impact despite lower density than that of neat PU foams. This is especially significant for multi-impact recurrences within the threshold loads and energies studied.